Diagnosis of urogenital gonorrhoea by detecting gonococcal antigen with a solid phase enzyme immunoassay (Gonozyme). Issue 6 (June 1983) - Danielsson, D; Moi, H; Forslin, L
Abstract : A solid phase enzyme immunoassay (Gonozyme) was used to demonstrate gonococcal antigen in urogenital specimens. Urethral specimens from 101 men and cervical specimens from 150 women were examined, and the diagnostic yields were compared with those obtained by culture. The Gonozyme test was positive in 25 patients, 15 men and 10 women, and negative in 226 patients. Gonococci were isolated by culture in 23 of the patients, 12 men and 11 women. The Gonozyme test gave false-negative results in two men and one woman patient. The sensitivity of the test was 87% for the men and 91% for the women. Correspondingly, the test specificity was 94.3% for the men and 100% for the women, the predictive value of positive test 80% and 100%, and that of negative test 97.7 and 99.3% respectively. The Gonozyme test does not allow antibiotic sensitivity testings but has the advantage of rapidity and is not dependent upon viable organisms. The test is an attractive alternative to culture procedures for screening women patients with symptomatic or asymptomatic gonorrhoea.